Answer: The solutions are
(0, 6)
(- 2, 0)
Step-by-step explanation:
The given system of equations is expressed as
y = x² + 5x + 6- - - - - - - - - - - - 1
y = 3x + 6- - - - - - - - - - - 2
We would apply the method of substitution by substituting equation 2 into equation 1. It becomes
x² + 5x + 6 = 3x + 6
x² + 5x - 3x + 6 - 6 = 0
x² + 2x = 0
x(x + 2) = 0
x = 0 or x + 2 = 0
x = 0 or x = - 2
Substituting x = 0 into equation 2, it becomes
y = 3 × 0 + 6
y = 6
Substituting x = - 2 into equation 2, it becomes
y = 3 × - 2 + 6
y = - 6 + 6
y = 0